DEVELOPMENTS OF PHYSICAL AND TECHNICAL INSTITUTE OF NAS OF BELARUS – TO THE INDUSTRIAL ENTERPRISES OF THE REPUBLIC - A. I. Gordienko; S. A. Astapchik; D. F. Ustinovich (Литьë и металлургия, 2011)
FTI NAS of Belarus – 80 years old